Mass spectrometry for the novice - Greaves, John (Director of Mass Spectrometry Facility); Roboz, John. 1931- (Boca Raton : CRC Press, 2014)
"Designed specifically for novice users of mass spectronomy, an audience that is not currently well-addressed by existing texts, this book covers the basic concepts, instruments, and techniques with cases illustrating its application in problem solving. Other books in this field focus too narrowly on instrumentation without discussing practical application, or present the information in dense discussions and tables, making the information hard to find. This book does neither, it provides practical advice and key background knowledge in a format that is easy to use"--
"Mass Spectrometry has grown immeasurably over the last twenty years. It may well be the technique to turn to if you want to analyze gases, pharmaceuticals, drugs of abuse, environmental pollutants, search for explosives at airports, to sequence peptides from proteins or understand the role of complex carbohydrates in cancer. There are an ever-increasing number of scientists coming into contact with the technique"--
Includes bibliographical references (pages 255-266) and index.
Keywords: Mass spectrometry; SCIENCE / Chemistry / Industrial & Technical; SCIENCE / Physics; MEDICAL / Biochemistry